Age validation of juvenile Notothenia rossii at Potter Cove, South Shetland Islands, using mark-recapture data - Moreira, María Eugenia; Barrera Oro, Esteban; La Mesa, Mario (Polar Biology)
Among all validation methods of age determination in fish, release of known age and marked specimens gives the most reliable information. We carried out a tag-recapture experiment on Notothenia rossii at Potter Cove, to validate, for first time for this species using this method, the principle of annual deposition of an annulus in scales and otoliths. Of 132 juvenile specimens (TL = 22.1–38.1 cm) tagged and released in successive years from 2004 to 2010, 7 were recaptured at the same site after periods of 1–13 months. In scales of five specimens recovered after 10–13 months, one extra annulus was laid down, exhibiting an additional winter zone of closely spaced sclerites. Consistently, the same analysis in two individuals marked and recaptured during the same summer, after 1–3 months at liberty, did not show the deposition of an additional annulus. All the fish tagged or recaptured during the experiment period (December to March) showed in their scales an edge zone of widely spaced sclerites, in agreement with the known pattern of growth in summer. Likewise, an analysis in selected specimens showed good consistency between the numbers of sclerites deposited in scales and the time of fish release. The comparative analysis between scales taken at recapture and otoliths of the same individual allowed a simultaneous counting of the annuli with complete correspondence. The growth in length of fish ranged from 0.5 to 6.1 cm, depending on the time of release. Fil: Moreira, María Eugenia. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Barrera Oro, Esteban. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales ...